2003
DOI: 10.1097/01.ccm.0000063145.15336.31
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of Candida krusei infection with caspofungin acetate: A new antifungal agent

Abstract: Efficacy of caspofungin acetate in a patient with life-threatening Candida Krusei infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
0
9
0
2
Order By: Relevance
“…Several authors have reported breakthrough infections due to C. krusei among patients receiving fluconazole or amphotericin B (1,11,19,21,31,34,61), and Goldman et al (9) found that response rates of C. krusei infection were significantly better for patients who had received amphotericin B in doses of Ն1 mg/kg of body weight per day than for those who had received lower doses. Furthermore, amphotericin B exhibits markedly delayed killing kinetics against C. krusei compared with that against Candida albicans (4,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported breakthrough infections due to C. krusei among patients receiving fluconazole or amphotericin B (1,11,19,21,31,34,61), and Goldman et al (9) found that response rates of C. krusei infection were significantly better for patients who had received amphotericin B in doses of Ն1 mg/kg of body weight per day than for those who had received lower doses. Furthermore, amphotericin B exhibits markedly delayed killing kinetics against C. krusei compared with that against Candida albicans (4,19).…”
mentioning
confidence: 99%
“…In addition, the echinocandins have been used based on their fungicidal activity and excellent in vitro activity against C. krusei (41,42,56,57). Whereas echinocandin antifungals such as caspofungin have been used successfully to treat several different infections involving C. krusei (21,28,31,34,50), there have been recent troubling reports of caspofungin failure in the treatment of C. krusei infections (10,15,33). Notably, Hakki et al (10) reported a strain of C. krusei from a leukemic patient that displayed reduced susceptibilities to caspofungin, anidulafungin, and micafungin.…”
mentioning
confidence: 99%
“…Caspofungin has demonstrated potent antifungal activity in vitro against Candida and Aspergillus isolates (4) and in vivo efficacy in mouse models of disseminated aspergillosis and candidiasis (1) as well as in a persistently neutropenic rabbit model of pulmonary aspergillosis (14). Caspofungin has been used successfully in the clinical arena for the treatment of candidiases as well as candidemia (2,7,12,13). Caspofungin has also been shown to be efficacious in the treatment of Aspergillus infections (11,15,17) and invasive aspergillosis in patients refractory or intolerant to amphotericin B (J. Maertens, I. Raad, C. A. Sable, A. Ngai, R. Berman, T. F. Patterson, D. Denning, and T. Walsh, Abstr.…”
mentioning
confidence: 99%
“…Die mukosale Candidiasis kann bei immunsupprimierten Menschen (z.B.transplantierte und HIV-infizierte Patienten) schwer verlaufen.In den letzten Jahren ersetzten neue Triazole (Fluconazol und Itraconazol) mit verbesserten WirkungsNebenwirkungs-Profilen bisher gängige Pilzmedikamente wie Amphotericin B und Nystatin [8,23,33].…”
Section: Candidainfektion Von Haut Und Schleimhautunclassified
“…Die klinische Antwort wird meist rasch innerhalb weniger Tage erreicht und selbst bei schweren Formen oraler Candidiasis ist die Ansprechrate hoch (Fluconazol je nach Schwere und ösophagealer Beteiligung höher dosiert mit 200-400 mg täglich peroral). Itraconazol-Suspension, 100-200 mg täglich peroral verabreicht, war ähnlich wirksam wie Fluconazol mit Ansprechraten von über 90% [8,12,23,31,33]. Allerdings ist wegen der Grundkrankheiten mit T-Zellfunktionsstörungen mit Rezidiven zu rechnen, sodass je nach Situation und Grunderkrankung eine Sekundärprophy-laxe anzuschließen ist.…”
Section: Risikofaktoren Für Candidainfekteunclassified